Exploring Priority Problems of the Forest Dependent Poor in Nepal - Luintel, Harisharan; Bhattarai, Basundhara (Journal of Forest and Livelihood, 2009)
This paper deals with the priority problems and their underlying causes of the forest and tree dependent poor - resource-poor farmers, landless, small artisan and urban/peri-urban poor - in Nepal, from their own and support agencies' perspectives. The paper is based on a survey conducted in seven districts of Nepal wherein 79 poor people and 65 staff members of support institutions were interviewed. The authors have identified the priority of the identified problems according to the frequency of their reference by the poor. These issues are discussed in seven categories, ranging from daily food insecurity to entrepreneurship development. The results demonstrate that the forest-dependent poor have diverse and complex livelihood related problems, which are frequently, but may not directly and exclusively, linked to forestry, per se. As such there is a need for a more continuous holistic and political approach encompassing not only economic but also cultural and social aspects for poverty reduction, in contrast with the existing technical, sectoral and linear approaches. Key words: forest and tree-dependent poor, priority problems, policy, Nepal doi: 10.3126/jfl.v5i1.1974 Journal of Forest and Livelihood 5(1) February, 2006 pp.1-13